Inpatient hypoglycaemia in older people is associated with a doubling in the increased length of stay compared with the younger population - Ruan, Y; Moysova, Z; Tan, GD; Lumb, A; Davies, J; Rea, R (Oxford University Press, 2020)
Background Hypoglycaemia during hospital admission is associated with poor outcomes including increased length of stay. In this study, we compared the incidence of inpatient hypoglycaemia and length of stays among people of three age groups: ≤65 years, 65–80 years and >80 years old.